Genetic characterization of the first Deltacoronavirus from wild birds around Qinghai Lake - Tian, Ye; Yu, Tianqi; Wang, Jun; Zhang, Haoxiang; Jian, Yingna; Li, Xiuping; Wang, Geping; Wang, Guanghua; Hu, Yong; Lu, Chenhe; Zhou, Jiyong; Ma, Liqing; et al. (Frontiers in Microbiology, 2024)
Deltacoronavirus, widely distributed among pigs and wild birds, pose a significant risk of crossspecies transmission, including potential human epidemics. Metagenomic analysis of bird samples from Qinghai Lake, China in 2021 reported the presence of Deltacoronavirus. A specific gene fragment of Deltacoronavirus was detected in fecal samples from wild birds at a positive rate of 5.94% (6/101). Next-generation Sequencing identified a novel Deltacoronavirus strain, which was closely related to isolates from the United Arab Emirates (2018), China (2022), and Poland (2023).Subsequently the strain was named A/black-headed gull/Qinghai/2021(BHG-QH-2021) upon confirmation of the Cytochrome b gene of black-headed gull in the sample. All available genome sequences of avian Deltacoronavirus, including the newly identified BHG-QH-2021 and 5 representative strains of porcine Deltacoronavirus (PDCoV), were classified according to ICTV criteria. In contrast to Coronavirus HKU15, which infects both mammals and birds and shows the possibility of cross-species transmission from bird to mammal host, our analysis revealed that BHG-QH-2021 is classified as Putative species 4. Putative species 4 has been reported to infect 5 species of birds but not mammals, suggesting that cross-species transmission of Putative species 4 is more prevalent among birds. Recombination analysis traced BHG-QH-2021 origin to dut148cor1 and MW01_1o strains, with MW01_1o contributing the S gene. Surprisingly, SwissModle prediction showed that the optimal template for receptor-binding domain(RBD) of BHG-QH-2021 is derived from the human coronavirus 229E, a member of the Alphacoronavirus, rather than the anticipated RBD structure of PDCoV of Deltacoronavirus. Further molecular docking analysis revealed that substituting the loop 1-2 segments of HCoV-229E significantly enhanced the binding capability of BHG-QH-2021 with human Aminopeptidase N (hAPN), surpassing its native receptor-binding domain (RBD). Most importantly, this finding was further confirmed by co-immunoprecipitation experiment that loop 1-2 segments of HCoV-229E enable BHG-QH-2021 RBD binding to hAPN, indicating that the loop 1-2 segment of the RBD in Putative species 4 is a probable key determinant for the virus ability to spill over into humans. Our results summarize the phylogenetic relationships among known Deltacoronavirus, reveal an independent putative avian Deltacoronavirus species with inter-continental and inter-species transmission potential, and underscore the importance of continuous surveillance of wildlife Deltacoronavirus.